Information Diffusion and Spillover Dynamics in Renewable Energy Markets - Samir Cedic; Alwan Mahmoud; Matteo Manera; Gazi Salah Uddin (Fondazione Eni Enrico Mattei (FEEM), 2021)
The aim of this paper is to analyze the connectedness between renewable energy (RE) sectors, the oil & gas sector and other assets using time-scale spillover approach. We find that the RE bioenergy firms are the most connected to oil & gas firms and oil prices. The bond market transmits spillover to the RE sectors, while it receives spillover from the oil & gas sector. Moreover, short-run connectedness drives the dynamic total connectedness. Since changes in bond rates mainly spillover to RE firms and not to oil & gas firms, policy makers should also be aware that changes in interest rates may impact the societal transition to a RE based energy system. Since a shock that increases connectedness in the short run will deter investors from investing in RE assets, it is important for climate policy makers to develop policies that reduce the effect of increased connectedness on RE investments.
Keywords: C1; G15; Q2; Q3; Q43; 330; Renewable Energy; Connectedness; Frequencies; Dynamics; Spillovers